De-dollarization of trade relations between China and Saudi Arabia with BRICS membership - Aboalghasem Shahryari; Marziye ALsadat Alvand; mahla moghani (رهیافتهای سیاسی و بین المللی)
Extended AbstractIntroduction: The fluctuations caused by the depreciation of the dollar along with the imposition of sanctions against countries using the power of the dollar have caused other countries to seek to reduce dependence on the dollar— a process known as de-dollarization. This is especially important for the People's Republic of China for two reasons: on the one hand, to counter the hegemony of the US dollar in international exchanges and transactions, and on the other hand, to  deal with the increasing energy security risks due to sanctions on China's oil suppliers. The purpose of this study is to examine China's actions towards de-dollarization through the establishment of the trans-regional BRICS organization and then to analyze the reasons behind Saudi Arabia's interest in joining this organization.Methods: The research method is trend analysis using time series and seeks to answer the question: What impact does BRICS membership have on the de-dollarization of trade between China and Saudi Arabia? The initial answer to the research question, which is the research hypothesis, is: the mechanisms designed in the BRICS by China will have a significant potential for Saudi Arabia to reduce dependence on the dollar.Results and discussion: Findings indicate that China has become the most important partner of Saudi oil exports during the period under review . In contrast, the consequences of sanctions against Iran and Russia have caused Saudi Arabia to try to reduce its dependence on the dollar. The processes within BRICS, especially trading in yuan on par with gold, have created the necessary capacity for Saudi Arabia to reduce its dependence on the dollar. At the same time, it should be noted that the measures taken by Saudi Arabia to expand cooperation with China are overshadowed by its relationship with the United States. Since Saudi Arabia is deeply integrated into the US-led economic and security framework, it cannot easily reduce its dependence on the dollar. Additionally, There is no intention at this time to abandon currency ties or end the defense partnership with the United States. For this reason, Saudi Arabia's long-term strategy is to develop the ability to conduct transactions in both the dollarized and de-dollarized regions, and to reduce its dependence on the United States while maintaining its position in the world energy distribution.Conclusions:The most important point about the process of de-dollarization and the efforts of organizations like BRICS, led by China, to counter the hegemony of the dollar is that de-dollarization has never meant abandoning the dollar. Instead, it is an attempt to diversify countries' currency reserves and increase the maneuverability of central banks in international exchanges and transactions. This is why China remains one of the largest  buyers of US Treasury bonds, despite its significant efforts to reduce the scope of the US dollar's power in international exchanges. In parallel, although it is unlikely that Saudi Arabia will be able to abandon the US dollar in the short and even medium term, it is nevertheless developing a broader financial instrument to reduce its dependence. Saudi Arabia has taken important steps such as designing a central bank digital currency, which plays an important role in the exchanges of BRICS members. Despite being in their early stages, central bank digital currencies appear to be a promising new tool to reduce the dependence of the dollar on regional and trans-regional cross-border transactions.